Detecting the major charge-carrier scattering mechanism in graphene antidot lattices. (April 2019) - Xu, Dongchao; Tang, Shuang; Du, Xu; Hao, Qing
Abstract: Charge carrier scattering is critical to the electrical properties of two-dimensional materials such as graphene, black phosphorene, and tellurene. Beyond pristine two-dimensional materials, further tailored properties can be achieved by nanoporous patterns such as nano- or atomic-scale pores (antidots) across the material. As one example, structure-dependent electrical/optical properties for graphene antidot lattices (GALs) have been studied in recent years. However, detailed charge carrier scattering mechanism is still not fully understood. In this paper, the energy sensitivity of charge-carrier scattering and thus the dominant scattering mechanisms are revealed for GALs by analyzing the maximum Seebeck coefficient with a tuned gate voltage and thus shifted Fermi levels. It shows that the scattering from pore-edge-trapped charges is dominant. For thermoelectric interests, the gate-voltage-dependent power factor for a GAL with the square pattern can reach as high as 554  μW / cm ⋅ K 2 at 400 K. With their high thermal conductivities and power factors, these GALs can be well suitable for "active coolers" within electronic devices, where heat generated at the hot spot can be removed with both passive heat conduction and active Peltier cooling. Graphical abstract: Measurement setup of GAL samples. The gate-voltage-dependent power factor of a GAL with the square pattern is measured as high as 554 μW/cm K 2 at 400 K on the hole side. Image 1